Genus-Specific Interactions of Bacterial Chromosome Segregation Machinery Are Critical for Their Function - Pióro, Monika; Matusiak, Izabela; Gawek, Adam; Łebkowski, Tomasz; Jaroszek, Patrycja; Bergé, Matthieu; Böhm, Kati; Armitage, Judith; Viollier, Patrick H.; Bramkamp, Marc; Jakimowicz, Dagmara (Frontiers in Microbiology, 2022)
Most bacteria use the ParABS system to segregate their newly replicated chromosomes. The two protein components of this system from various bacterial species share their biochemical properties: ParB is a CTPase that binds specific centromere-like parS sequences to assemble a nucleoprotein complex, while the ParA ATPase forms a dimer that binds DNA non-specifically and interacts with ParB complexes. The ParA-ParB interaction incites the movement of ParB complexes towards the opposite cell poles. However, apart from their function in chromosome segregation, both ParAB may engage in genus-specific interactions with other protein partners. One such example is the polar-growth controlling protein DivIVA in Actinomycetota, which binds ParA in Mycobacteria while interacts with ParB in Corynebacteria. Here, we used heterologous hosts to investigate whether the interactions between DivIVA and ParA or ParB are maintained across phylogenic classes. Specifically, we examined interactions of proteins from four bacterial species, two belonging to the Gram positive Actinomycetota phylum and two belonging to the Gram-negative Pseudomonadota. We show that while the interactions between ParA and ParB are preserved for closely related orthologs, the interactions with polarly localised protein partners are not conferred by orthologous ParABs. Moreover, we demonstrate that heterologous ParA cannot substitute for endogenous ParA, despite their high sequence similarity. Therefore we conclude that ParA orthologs are fine-tuned to interact with their partners, especially their interactions with polarly localised proteins are adjusted to particular bacterial species demands.